Frontiers of gender equality: transnational legal perspectives - Cook, Rebecca J.; Medina Quiroga, Cecilia (Pennsylvania studies in human rights, 2023)
"The book provides retrospective views of the struggles to eliminate gender discrimination in national courts and international human rights treaties. Focusing on gender equality enables comparisons and contrasts among these regimes to better understand how they reinforce gender equality norms. Different regional and international treaties are examined, those in the forefront of advancing gender equality, those that are promising but little known, and those whose focus includes economic, social and cultural rights, to explore why some struggles were successful and others less so. The book illustrates how gender discrimination continues to be normalized and camouflaged, and how it intersects with other axes of subordination, such as indigeneity, religion and poverty, to create new forms of intersectional discrimination"--